Performa Pertumbuhan Dan Kelangsungan Hidup Ikan Seluang (Brevibora Cheeya) Dalam Adaptasinya Pada Lingkungan Buatan - Nia Sahra; Suharni Suharni; Anggun Lestari; Ardiansyah Kurniawan (CV. SINAR HOWUHOWU, 2025)
The utilization of seluang fish (Brevibora cheeya) from the Jade River waters to date still relies on wild catches, so domestication efforts are needed to maintain population sustainability. This study aims to determine the level of domestication in Brevibora cheeya fish and become an effective solution to preserve local fish species and strengthen the existence of local fish. The research method used was a descriptive experiment conducted for 30 days at the Hatchery of Bangka Belitung University. Test samples of 21 fish from the Jade River were kept in containers with a filtration system and fed PF 800 pellets ad libitum. Parameters observed included growth in length, weight, survival rate, and water quality. The results showed that the domestication process had only reached level 2, where fish were able to adapt but growth was still relatively slow. The average length of fish increased from 4.42 cm to 4.68 cm and the average weight increased from 1 gram to 1.8 grams. The survival rate (SR) was recorded at 52%, with a relatively high Feed Conversion Ratio (FCR). Water quality factors, particularly an average temperature of 25.9°C and a pH of 6.10, were within the tolerance range, although suspected to be limiting factors for optimal growth.